Research status and thinking on the application of moxibustion therapy in cancer patients undergoing chemotherapy (艾灸疗法在肿瘤化疗患者中的应用研究现状与思考) - MEI Yuwei (梅雨薇); ZHANG Mi (张秘); Li Yingjie (李迎杰); WANG Xue (王雪); WANG Zhihao (王志豪) (Association of Integrative Nursing, 2023)
Chemotherapy is a common treatment for cancer, but the impact of side effects on the quality of life of patients is also the main problem that needs attention. This paper summarized the research status of moxibustion therapy in treatment of chemotherapy-related adverse reactions such as digestive tract reaction, peripheral neuropathy and bone marrow suppression, and provided reference for improvement of efficacy, safety and normalization of moxibustion therapy in cancer patients undergoing chemotherapy. (化疗是目前治疗肿瘤患者较为常用方法, 化疗后相关反应严重影响患者生活质量。本研究总结艾灸疗法在治疗化疗导致的消化道反应、周围神经病变、骨髓抑制等不良反应中的应用现状, 旨在为提高肿瘤患者化疗过程中应用艾灸疗法的有效性、安全性、规范性提供参考。)